2015
DOI: 10.1186/s40663-015-0059-y
|View full text |Cite
|
Sign up to set email alerts
|

Susceptible conditions for debarking by deer in subalpine coniferous forests in central Japan

Abstract: Background: Recently, deer have expanded their distribution to higher altitude ranges including subalpine forests. However, culling deer and construction of deer fence in subalpine forests are difficult because of steep slopes and complex topography. Thus it is necessary to clarify the factors which are associated with debarking by deer for the effective protection of subalpine forests. In this study, we examined which factors are associated with debarking by sika deer (Cervus nippon) in subalpine coniferous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Deciduous forest comprised broad-leaved species (e.g., Acer , Betula , and Quercus ) in 76% of area, and a coniferous species ( Larix kaempferi ) in 24% of the area ( Iijima and Nagaike 2015a ). In Yamanashi Prefecture, the population density of C. nippon had increased in recent years ( Iijima et al 2013 ), resulting in extensive debarking of trees ( Nagaike and Hayashi 2003 ; Iijima and Nagaike 2015b ) and browsing of understory vegetation in forests ( Iijima and Nagaike 2015a ) and subalpine grassland ( Nagaike 2012 ).…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…Deciduous forest comprised broad-leaved species (e.g., Acer , Betula , and Quercus ) in 76% of area, and a coniferous species ( Larix kaempferi ) in 24% of the area ( Iijima and Nagaike 2015a ). In Yamanashi Prefecture, the population density of C. nippon had increased in recent years ( Iijima et al 2013 ), resulting in extensive debarking of trees ( Nagaike and Hayashi 2003 ; Iijima and Nagaike 2015b ) and browsing of understory vegetation in forests ( Iijima and Nagaike 2015a ) and subalpine grassland ( Nagaike 2012 ).…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…The study site was the whole of Yamanashi Prefecture, central Japan. In Yamanashi Prefecture, the population density of sika deer has increased in recent years (Iijima and Ueno 2016), resulting in extensive debarking of trees (Nagaike andHayashi 2003, Iijima andNagaike 2015b) and browsing of understory vegetation in forests (Iijima and Nagaike 2015a) and herbaceous grasses in subalpine grasslands (Nagaike 2012). The hunting season in Yamanashi Prefecture is from November to March, and registered hunters hunt sika deer by shooting or trapping (snaring the legs).…”
Section: Study Sitementioning
confidence: 99%
“…A few studies have indicated the existence of genetic variation in needle herbivory by mammals [22,[27][28][29] but not for bark damage. Mammalian bark stripping has been reported on various conifers, including Pinus radiata, where it impacts the forest industry through its effect on growth, reproduction, and survival as well as its effect on the timber quality resulting from wood decay [6,[30][31][32]. However, most studies of mammalian bark stripping in conifers have been undertaken at the phenotypic level, and at this stage there are no studies at the genetic level.…”
Section: Introductionmentioning
confidence: 99%